2021
DOI: 10.3897/neobiota.67.59116
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of biological invasions in Ecuador: the importance of the Galapagos Islands

Abstract: Biological invasions, as a result of human intervention through trade and mobility, are the second biggest cause of biodiversity loss. The impacts of invasive alien species (IAS) on the environment are well known, however, economic impacts are poorly estimated, especially in mega-diverse countries where both economic and ecological consequences of these effects can be catastrophic. Ecuador, one of the smallest mega-diverse countries, lacks a comprehensive description of the economic costs of IAS within its ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 77 publications
(87 reference statements)
1
13
0
Order By: Relevance
“…Yet, the direct medical costs resulting from the expanding populations of vector mosquitoes remain poorly documented. High costs for Aedes species were expected in the French territories located in the Americas (French Guiana, Martinique and Guadeloupe), as these species were also the costliest species in the Central and South America region and in specific countries therein such as Ecuador or Argentina (Ballesteros-Mejia et al 2021;Duboscq-Carra et al 2021;Heringer et al 2021). For these French territories in the Americas, Uhart et al (2016) documented 4,574 hospitalisations of approximately 4.3 days each for patients affected by dengue, with a mean cost per stay of US$ 2,849.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the direct medical costs resulting from the expanding populations of vector mosquitoes remain poorly documented. High costs for Aedes species were expected in the French territories located in the Americas (French Guiana, Martinique and Guadeloupe), as these species were also the costliest species in the Central and South America region and in specific countries therein such as Ecuador or Argentina (Ballesteros-Mejia et al 2021;Duboscq-Carra et al 2021;Heringer et al 2021). For these French territories in the Americas, Uhart et al (2016) documented 4,574 hospitalisations of approximately 4.3 days each for patients affected by dengue, with a mean cost per stay of US$ 2,849.…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, Duboscq-Carra et al (2021) found an accumulated cost USD 5.5 million higher than us for Argentina (USD 6,907.6 million vs. USD 6,902.1 million). Conversely, Ballesteros-Mejia et al (2021) found smaller costs for Ecuador because one of the entries with high economic impact was classified in their study as low reliability and therefore removed from the main analyses (USD 86.2 million vs. USD 604.9 million; see details at Ballesteros-Mejia et al 2021). In country-level assessments with limited data availability, it is essential to use all available data for the most comprehensive assessment possible.…”
Section: General Patternsmentioning
confidence: 95%
“…97% for France, Renault et al 2021; 69% for Germany, Haubrock et al 2021b). For instance, in Central and South America over 40% of cost estimates came from Spanish and Portuguese sources (Heringer et al 2021); and in Ecuador 51.8% of the costs were reported in Spanish (Ballesteros-Mejia et al 2021). An extreme situation is observed in Japan, where all recorded costs were in Japanese (Watari et al 2021), although this was a common trend in Asia (reviewed in Liu et al 2021).…”
Section: General Costs Of Ias In Spainmentioning
confidence: 99%